Maladaptation and phenotypic mismatch in hatchery‐reared Atlantic salmon Salmo salar released in the wild - R. Stringwell; A. Lock; C. J. Stutchbury; E. Baggett; J. Taylor; P. J. Gough; C. Garcia de Leaniz (Journal of Fish Biology, 2014)
Changes in body shape, fluctuating asymmetry ( FA ) and crypsis were compared among Atlantic salmon Salmo salar fry kept as controls in captivity and those released and subsequently recaptured in the wild according to a before‐after‐control‐impact ( BACI ) design. Hatchery fish that survived in the wild became more cryptic and displayed a much lower incidence of fin erosion and of asymmetric individuals than control fish kept in captivity. Significant differences in body shape were also apparent, and survivors had longer heads, thicker caudal peduncles and a more streamlined body shape than hatchery controls as early as 20 days following stocking, most likely as a result of phenotypic plasticity and non‐random, selective mortality of maladapted phenotypes. Hatchery‐reared fish typically perform poorly in the wild and the results of this study indicate that this may be due to phenotypic mismatch, i.e. because hatcheries generate fish that are phenotypically mismatched to the natural environment.